BIMBINGAN PRIBADI SOSIAL UNTUK MENGEMBANGKAN KEMAMPUAN PENYESUAIAN DIRI SISWA - Hendra Abdul Karim; Mohammad Salehudin (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2021)
Abstract:Every student is required to be able to adjust to the social environment. Social adjustment in students is certainly not easy to do, this is due to a lack of good self-understanding, so social personal guidance is needed so that it can help students in solving problems that will occur. The purpose of this study is to find out insight into the understanding of the importance of adjusting students to their environment. This research uses a descriptive qualitative approach with the type of library research (Library Research). Social self-adjustment is a process of adaptation to the environment. In overcoming students' social adjustment problems, social personal guidance programs can be realized through systematic servants in the counseling process. Social personal guidance is an effort to help in dealing with various social problems that exist in the individual. It can be concluded that the services provided can help students develop students' adjustment abilities.